1993
DOI: 10.1111/j.1574-6968.1993.tb06156.x
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous germination of Streptomyces antibioticus spores: Tool for the analysis of hyphal growth in liquid cultures

Abstract: We have devised a method for obtaining synchronous and dispersed growth of Streptomyces antibioticus in liquid cultures. After ultrasonic treatment, most of the spores germinated at the same time, yielding hyphae very similar in length. Dispersed growth was achieved in media without Ca2+ and in which the levels of Fe2+ and Mg2+ were carefully controlled. Studies on the kinetics of growth carried out with synchronous cultures of young hyphae revealed a multiphasic pattern of hyphal elongation, with successive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 10 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Although heat shock 57 and ultrasonic treatments 58 may increase the germination rates of streptomycetes, very little is known about the germination mechanism. We found that the 12 MHz sine-wave potential induced the maximum number of CFUs in the attached ST.28 spores and increased the germination rate by 2.8 fold (Fig.…”
mentioning
confidence: 99%
“…Although heat shock 57 and ultrasonic treatments 58 may increase the germination rates of streptomycetes, very little is known about the germination mechanism. We found that the 12 MHz sine-wave potential induced the maximum number of CFUs in the attached ST.28 spores and increased the germination rate by 2.8 fold (Fig.…”
mentioning
confidence: 99%